Education on Sedentary Lifestyle, Nutritional Status, and Metabolic Syndrome Among Students - Prasetyo, Muhammad Purwono; Wardhana, Carbela Zahra; Lestari, Dharma Lina; Putri, Nandini Amerta; Hening, Putik Titian Citra; Islami, Suryadi (Jurnal Abmas Negeri (JAGRI), 2025)
Sedentary lifestyle and imbalanced nutritional status are major risk factors for metabolic syndrome, including among adolescents. Currently, many adolescents experience a lack of physical activity due to various factors, including excessive use of gadgets, prolonged sitting during study, and unhealthy eating habits. This community service activity aimed to educate students of Ar-Raihan Boarding School, Lampung, regarding sedentary lifestyle, nutritional status, and the prevention of metabolic syndrome. The methods included health promotion through interactive counseling, simple nutritional status assessment using Body Mass Index (BMI) measurement, blood pressure examination, and random blood glucose examination, as well as group discussions. The health education activities were successfully implemented and received positive responses from students. Screening results showed variations in nutritional status and health conditions that served as the basis for providing educational feedback. After the intervention, students demonstrated increased understanding of sedentary lifestyle risk factors and the importance of adopting a healthy lifestyle to prevent metabolic syndrome. This health education program is expected to be implemented sustainably to support the development of healthy behaviors from adolescence.